PERANCANGAN PROTOTIPE ALAT UKUR ARUS LISTRIK AC DAN DC BERBASIS MIKROKONTROLER ARDUINO DENGAN SENSOR ARUS ACS-712 30 AMPERE - titi ratnasari; Adri Senen (Sekolah Tinggi Teknik - PLN, 2018)
Measuring tool can be defined as a tool that can know the value of used in a unit based on the level of accuracy. Household electric current measuring devices are often used now still use analog systems are slightly complicated in terms of reading the value of the output, it's because the viewer uses a needle that points at a certain scale. Besides the current measuring device ac and dc electricity in the market generally, very rarely menggunkana microcontroller. Based on that the authors designed an ac and dc based arduino uno power meter is using the current sensor acs 712 30 amps. This tool takes the working principle of the amperemeter, ie the principle of magnetic force (lorentz style). It's just different from the multimeter that uses a probe as a current conductor medium, this tool uses the terminals as a medium of conductor current. This tool can be used to measure all household electronic appliances or offices either AC or DC current.